The Effort to Realize Government Effectiveness Through Implementation Fully Accrual Accounting and Control Against Corruption - Siti Faradila S. Saud; Andi Chairil Furqan (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2024)
Introduction/Main Objectives: This study aims to analyze how far the influence of the implementationof the accrual accounting public sector on the Government and control of corruption could increasegovernment effectiveness. Background Problems: This means that countries that fully adoptedaccrual accounting and had control of corruption (a high Corruption Perception Index score) tend tohave better government effectiveness, and vice versa. Research Methods: Using cross-country datafor 2020 with a final sample of 194 countries. Finding/Results: This study shows that the accrualaccounting public sector and the Corruption Perception Index (CPI) positively affect governmenteffectiveness. Conclusion: Therefore, to increase government effectiveness, it was necessary to makeeffective law enforcement and control strategies to prevent corruption.